Prince Wan's Mission in the Hungarian Problem Wrecked - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. The Hungarian question was placed on the agenda on the 12th Session but did not come up for discussion, and instead was placed in a hurry on the agenda of the 13th Session. Neue Zürcher Zeitung report.